Mixing in a co‐current upflow bubble column reactors with and without internals. (26th March 2018) - Bhusare, Vishal H.; Kalaga, Dinesh V.; Dhiman, Mukesh K.; Joshi, Jyestharaj B.; Roy, Shantanu
Abstract: Liquid phase mixing is a phenomenon that results mainly due to convective and turbulent flow fields, which are generated by hydrodynamic interactions between the gas and liquid phases within a continuous co‐current upflow bubble column reactor. The extent of liquid phase mixing is usually quantified through the mixing time, or the axial dispersion coefficient. In the present work, the computational fluid dynamics (CFD) simulations for mixing and RTD in a continuous bubble column (with and without internals) are performed by using OpenFOAM 2.3.1. The superficial gas velocities were 0.014, 0.088, and 0.221 m/s and the superficial liquid velocities were 0.005 and 0.014 m/s. The simulations have been performed for three different configurations of the bubble column, that is, (a) an open bubble column, (b) a column with one vertical central rod of 36 mm diameter, (c) a column with the same central rod and four vertical additional rods of 12 mm diameter. The effects of superficial gas and liquid velocities and column internals were investigated on liquid phase mixing and the axial dispersion coefficient. Comparisons have been made between the experimental measurements and the CFD simulations.